Homocysteinemia in Heart Failure - Adnan Khaleefah, Mohammed; Ibrahim Latif, Ismail; Mousa Jaffar, Ali (Diyala Journal of Medicine, 2021)
Background: Heart failure represents a major health problem leading to considerable mortality morbidity. High total homocysteine concentrations have been related to increased risk of atherosclerosis and its sequel, including coronary heart disease, cardiovascular mortality, and stroke. Brain Natriuretic peptide is a member of a group of peptide hormones similar in structure, used as a specific marker for diagnosing heart failure. This marker increases gradually with the progression of the grade of heart failure. Objective: The current study aims to measure and investigate the difference in the level of homocysteine between patients with heart failure and without, to find the relationship between the level of homocysteine and grade of heart failure, and to find out the correlation between homocysteine levels with Brain Natriuretic peptide levels. Patients and Methods: This case-control study involved 200 participants, 100 patients with a history of chronic heart failure, and 100 control participants.A self-constructed questionnaire form prepared to collect selected variables, the participant’s weight, height, temperature, electrocardiography measured by trained staff, Brain Natriuretic peptide used as a specific marker for diagnosing heart failure. Blood samples were taken early in the morning from the patient and control groups, after at least 12-hours of fasting and a 20-minute rest. Analysis of all samples of blood was performed in the Biochemistry Laboratory of Baqubah teaching hospital to measure the levels of homocysteine by Human Homocysteine ELISA kit. Results: The sample was selected homogenously in terms of age and gender. Overweight, obesity, current and ex-smoker, history of hypertension, and history of diabetes mellitus were significantly higher in patients with heart failure than control. The fasting mean homocysteine level was significantly higher in patients (20.049nmol/ml) than in control (2.734nmol/ml). The fasting mean homocysteine level was significantly elevated in the patients with a positive history of hypertension and diabetes mellitus (p-value ≤0.05) than patients with a negative history. The level of homocysteine was correlated significantly and positively with the level of Brain Natriuretic peptide(r=0.39, p=0.001). The fasting mean homocysteine level was significantly increased with an increase in the severity (grades) of the heart failure (p-value = 0.001). Conclusion: There was a relationship between the homocysteine level with the development, and severity (grades) of the heart failure as well as significantly and positively correlated with the Brain Natriuretic peptide level.